Preparation method of antireflection film with ultralow refractive index and film blowing device
By combining sol-gel method and blown film method, a hydrophobic SiO2 film with adjustable refractive index was prepared, solving the problem of difficulty in preparing ultra-low refractive index porous SiO2 materials in the prior art, and achieving an efficient and environmentally friendly preparation process.
Patent Information
- Application Number
- CN202510037000.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to quickly and conveniently prepare ultra-low refractive index porous SiO2 materials under mild environments, and common methods have high costs and are not suitable for large-scale preparation or use of toxic chemicals.
Hollow SiO2 nanosphere sol was prepared by sol-gel method, and in-situ modification was performed by the introduction of methyl triethoxysilane, and hydrophobic SiO2 films with adjustable refractive index were prepared in combination with the blown film method.
The SiO2 film with a refractive index as low as 1.08 was prepared under mild conditions, while improving the hydrophobicity and environmental stability of the film, avoiding template removal and the use of hazardous chemicals.
Smart Images

Figure CN119819550A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical technology, and in particular relates to a method for preparing an ultra-low refractive index anti-reflection film and a film blowing device. Background Art
[0002] Nanoporous materials have been widely used in anti-reflection films, distributed Bragg reflectors, etc. However, due to the lack of ultra-low refractive index optical materials, especially the lack of optical materials with a refractive index close to the refractive index of air, the realization of related application devices with excellent optical performance has been hindered. Therefore, up to now, a large number of research works have been carried out on the preparation of ultra-low refractive index materials. Among them, physical vapor deposition is the most commonly used technology, but this preparation method has high equipment cost requirements and is not suitable for large-area preparation. In addition, the mesoporous method can be used to prepare porous SiO2 films with ultra-low refractive index (1.19) and high transparency, but the high-temperature calcination in the coating process is not suitable for polymer substrates and will also produce stress on glass substrates. For example, patent CN110196271A discloses a mesoporous composite film electrode containing gold nanoparticles, a preparation method and an application. Under a certain deposition voltage and deposition time, a dense mesoporous silica film is formed on the surface of a conductive substrate, which is rinsed with deionized water, dried and then calcined to obtain a mesoporous silica film / conductive substrate electrode, but the high-temperature calcination in the coating process is not suitable for polymer substrates and will produce stress on glass substrates. Glass substrates also produce stress; chemical etching with hydrofluoric acid solution can obtain SiO2 thin films with low refractive index, but the process involves the use of toxic and harmful etchants, which is not conducive to large-scale production. For example, a silicon dioxide film etching solution disclosed in CN111471463B can be used to etch silicon dioxide films grown by thermal oxidation, silicon dioxide films grown by chemical vapor deposition / physical vapor deposition, and borophosphorus silicon glass films. By regulating the content of each component in the etching solution, the etching index requirements of silicon dioxide films of different processes can be met, but the process involves the use of toxic and harmful etchants, which is not conducive to large-scale production. Therefore, it is very necessary to quickly and conveniently prepare ultra-low refractive index porous SiO2 materials under mild conditions. As we all know, the sol-gel method is a very promising method for preparing porous SiO2 materials because of its low operating temperature, low cost, high purity, and no strict requirements on the size and shape of the substrate. Studies have shown that the refractive index of the film can be controlled by changing the content of non-polar groups (such as methyl and trimethylsilyl (-Si(CH3)3)) in the raw materials. The introduction of the above non-polar groups can effectively prevent the collapse of the pores and reduce the surface energy of the film, making it have excellent anti-reflection properties and good hydrophobicity, but the lowest refractive index value of the film can only be reduced to 1.19. Therefore, how to further reduce the refractive index of the film under mild conditions and at the same time give the film excellent optical properties and good hydrophobicity is still an urgent problem to be solved. Summary of the invention
[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0004] In order to achieve these purposes and other advantages according to the present invention, a method for preparing an ultra-low refractive index anti-reflection film is provided, characterized in that it comprises the following steps:
[0005] Step 1: Mix polyacrylic acid, anhydrous ethanol and ammonia water, and then add a certain amount of tetraethyl orthosilicate to react and age;
[0006] Step 2: adding methyltriethoxysilane to the aged sol, stirring the mixture thoroughly, and letting the mixture stand to obtain a modified sol;
[0007] Step 3: Use a plasma cleaning machine to perform plasma cleaning on the substrate, and then use the constructed film blowing device to plate the modified sol on the substrate to form a thin film.
[0008] Preferably, in step 1, the mass volume ratio of polyacrylic acid, anhydrous ethanol, ammonia water and tetraethyl orthosilicate is 0.01-1 g:150-200 mL:5-15 mL:1 mL.
[0009] Preferably, in the step 1, when adding tetraethyl orthosilicate, 0.2 mL of tetraethyl orthosilicate is added every 1 hour and aged for 48 to 72 hours.
[0010] Preferably, in the step 2, the amount of methyltriethoxysilane added is 0.1-1 mL, stirred at 30° C. for 2 h, and aged for 7 days.
[0011] Preferably, in step three, the plasma cleaning power is 30 W and the cleaning time is 5 min.
[0012] Preferably, the specific steps of step three are: use the constructed film blowing device to fix the substrate, control the substrate spacing to 2 mm, inject an appropriate amount of sol with a syringe, slowly push the syringe to make the sol bubble slowly, and use a stable nitrogen flow rate of 250 mL / min to push the injected sol to bubble, so that it slides evenly on the substrate surface to coat an ultra-low refractive index SiO2 film.
[0013] The present invention also provides a film blowing device, comprising: a fixed frame, on which two substrates are detachably connected, an air injection device is arranged above the substrates, and the air injection device contains modified sol.
[0014] Preferably, in the step 1, after the polyacrylic acid, anhydrous ethanol and ammonia water are mixed and stirred evenly, a certain amount of tetraethyl orthosilicate and citric acid solution are added to react, when the tetraethyl orthosilicate is added, 0.2 mL of the tetraethyl orthosilicate is added every 1 hour, and the concentration of the citric acid solution is 5-10wt%. When the citric acid solution is added, 0.2 mL is also added together with the tetraethyl orthosilicate every 1 hour, and the citric acid solution is aged to obtain a hollow SiO2 nanosphere sol.
[0015] Preferably, after the SiO2 film is prepared, it is post-processed, comprising the following steps:
[0016] S1, dissolving a small molecule fluorine-containing compound and polyethyl methacrylate in toluene to prepare a spraying liquid;
[0017] S2. Use a low-pressure sprayer to evenly spray the spray liquid onto the SiO2 film.
[0018] Preferably, the small molecule fluorine-containing compound is one or more of hexafluorobutyl acrylate, hexafluorobutyl methacrylate or heptafluorobutyl acrylate, and the mass ratio of the small molecule fluorine-containing compound, ethyl methacrylate and toluene is 0.5-1:0.1-0.5:100.
[0019] The present invention includes at least the following beneficial effects: hollow SiO2 nanospheres (HSNs) sol is prepared by sol-gel method, and HSNs sol is modified in situ by methyltriethoxysilane (MTES), and hydrophobic SiO2 film with adjustable refractive index is prepared by film blowing method, and the refractive index of the prepared film is as low as 1.08 by changing the molar ratio of methyltriethoxysilane and tetraethyl orthosilicate (TEOS); by introducing methyl groups on HSNs, the water contact angle is increased from 45° to 125°, thereby improving the hydrophobicity and environmental stability of the film. While preparing a film with ultra-low refractive index, excellent optical properties and hydrophobicity, the invention avoids template removal and the use of hazardous chemicals, and the preparation conditions are very mild. The above-mentioned SiO2 film with adjustable refractive index and environmental stability has broad application prospects in high-power laser systems.
[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 TEM image of the sol prepared in Example 1 of the present invention;
[0022] Figure 2 This is a schematic diagram of a film blowing device according to Example 1 of the present invention;
[0023] Figure 3A graph showing the variation of the refractive index of SiO2 films prepared in Examples 1 to 5 of the present invention and Comparative Example 1 with the molar ratio of MTES / TEOS;
[0024] Figure 4 This is a water contact angle diagram of the SiO2 film prepared in Example 1 of the present invention;
[0025] Figure 5 This is a water contact angle diagram of the SiO2 film prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0027] Example 1
[0028] A film blowing device comprises: a fixed frame 1, on which two substrates 2 are detachably connected, an air injection device 3 is arranged above the substrates 2, and a modified sol 4 is contained in the air injection device.
[0029] Working principle: After mounting two substrates 2 on a fixed frame 1, control the substrate spacing to be 2 mm, load the modified sol 4 into the gas injection device 3, and use the gas injection device 3 to inject the modified sol 4 between the two substrates 2. Use nitrogen at a stable flow rate of 250 mL / min to push the injected modified sol 4 to bubble, so that it slides evenly on the surface of the substrate 2, and an ultra-low refractive index SiO2 film is deposited on the surface of the substrate 2.
[0030] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0031] Step 1: Dissolve 0.06 g of polyacrylic acid (PAA) in 7 mL of ammonia water, then add it to 180 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate (TEOS) every 1 h, and add 1 mL of tetraethyl orthosilicate in total. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0032] Step 2: Add 0.7 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0033] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2The film blowing device shown in the figure mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, injects the modified sol into the space between the two substrates with the gas injection device, and pushes the injected sol to bubble with a stable nitrogen gas flow rate of 250 mL / min, so that it slides evenly on the substrate surface, and deposits an ultra-low refractive index SiO2 film, whose water contact angle is as follows: Figure 4 As shown, it is 124.99°; the film hardness of the SiO2 film is 2H.
[0034] Example 2
[0035] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0036] Step 1: Dissolve 0.02 g of polyacrylic acid (PAA) in 5 mL of ammonia water, then add it to 150 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate every 1 h, and add a total of 1 mL of tetraethyl orthosilicate. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0037] Step 2: Add 0.9 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0038] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2 The film blowing device shown in the figure mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, and uses the gas injection device to inject the modified sol into the space between the two substrates, and uses a stable nitrogen gas flow rate of 250 mL / min to push the injected sol to bubble, so that it slides evenly on the substrate surface, and an ultra-low refractive index SiO2 film is deposited, and the film hardness of the SiO2 film is 2H.
[0039] Example 3
[0040] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0041] Step 1: Dissolve 0.09 g of polyacrylic acid (PAA) in 14 mL of ammonia water, then add it to 180 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate every 1 h, and add a total of 1 mL of tetraethyl orthosilicate. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0042] Step 2: Add 0.4 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0043] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2 The film blowing device shown in the figure mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, and uses the gas injection device to inject the modified sol into the space between the two substrates, and uses a stable nitrogen gas flow rate of 250 mL / min to push the injected sol to bubble, so that it slides evenly on the substrate surface, and an ultra-low refractive index SiO2 film is deposited, and the film hardness of the SiO2 film is 2H.
[0044] Example 4
[0045] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0046] Step 1: Dissolve 0.04 g of polyacrylic acid (PAA) in 6 mL of ammonia water, then add it to 160 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate every 1 h, and add a total of 1 mL of tetraethyl orthosilicate. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0047] Step 2: Add 0.3 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0048] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2 The film blowing device shown in the figure mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, and uses the gas injection device to inject the modified sol into the space between the two substrates, and uses a stable nitrogen gas flow rate of 250 mL / min to push the injected sol to bubble, so that it slides evenly on the substrate surface, and an ultra-low refractive index SiO2 film is deposited, and the film hardness of the SiO2 film is 2H.
[0049] Example 5
[0050] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0051] Step 1: Dissolve 0.01 g of polyacrylic acid (PAA) in 5 mL of ammonia water, then add it to 150 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 hours. During the stirring period, add 0.2 mL of tetraethyl orthosilicate every 1 hour, and add a total of 1 mL of tetraethyl orthosilicate. After the stirring reaction is completed, age it for 48 hours to obtain HSNs sol;
[0052] Step 2: Add 0.1 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0053] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2 The film blowing device shown in the figure mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, and uses the gas injection device to inject the modified sol into the space between the two substrates, and uses a stable nitrogen gas flow rate of 250 mL / min to push the injected sol to bubble, so that it slides evenly on the substrate surface, and an ultra-low refractive index SiO2 film is deposited, and the film hardness of the SiO2 film is 2H.
[0054] Example 6
[0055] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0056] Step 1: Dissolve 0.06 g of polyacrylic acid (PAA) in 7 mL of ammonia water, then add it to 180 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate and 0.2 mL of 10 wt% citric acid solution every 1 h, and add 1 mL of tetraethyl orthosilicate and 1 mL of citric acid solution in total. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0057] Step 2: Add 0.7 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0058] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2 The film blowing device shown mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, injects the modified sol into the space between the two substrates using the gas injection device, and pushes the injected sol to bubble with a stable nitrogen flow rate of 250 mL / min, so that it slides evenly on the substrate surface, thereby coating an ultra-low refractive index SiO2 film.
[0059] The water contact angle of the SiO2 film prepared in this embodiment is 125.02°, and its hydrophobicity is close to that of Example 1, but the film hardness of the SiO2 film is improved to 3H.
[0060] Example 7
[0061] A method for preparing an ultra-low refractive index anti-reflection film comprises the following steps:
[0062] Step 1: Dissolve 0.06 g of polyacrylic acid (PAA) in 7 mL of ammonia water, then add it to 180 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate and 0.2 mL of 10 wt% citric acid solution every 1 h, and add 1 mL of tetraethyl orthosilicate and 1 mL of citric acid solution in total. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0063] Step 2: Add 0.7 mL of methyltriethoxysilane (MTES) to the HSNs sol, stir the mixed sol at 30° C. for 2 h, and age for 7 days to obtain a modified sol;
[0064] Step 3: Use PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes; then build Figure 2 The film blowing device shown mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, injects the modified sol into the space between the two substrates using the gas injection device, and pushes the injected sol to bubble with a stable nitrogen flow rate of 250 mL / min, so that it slides evenly on the substrate surface, thereby coating an ultra-low refractive index SiO2 film.
[0065] The SiO2 film is post-processed, comprising the following steps:
[0066] S1. Dissolve 0.5 g of hexafluorobutyl methacrylate and 0.5 g of polyethyl methacrylate in 100 g of toluene to prepare a spraying liquid;
[0067] S2. Use a low-pressure sprayer to evenly spray a layer of the spray liquid on the SiO2 film. After natural drying, a post-treated SiO2 film is obtained.
[0068] The water contact angle of the SiO2 film prepared in this embodiment is 145.84°, and the hydrophobicity is further improved. At the same time, the film hardness of the SiO2 film also reaches 3H.
[0069] Comparative Example 1
[0070] Step 1: Dissolve 0.06 g of polyacrylic acid (PAA) in 7 mL of ammonia water, then add it to 180 mL of anhydrous ethanol, and stir it magnetically at 30 ° C for 7 h. During the stirring period, add 0.2 mL of tetraethyl orthosilicate every 1 h, and add a total of 1 mL of tetraethyl orthosilicate. After the stirring reaction is completed, age it for 48 h to obtain HSNs sol;
[0071] Step 2: Use a PCE-6 plasma cleaning machine to perform plasma cleaning on the substrate, with a cleaning power of 30W and a cleaning time of 5 minutes;
[0072] Step 3, then build Figure 2 The film blowing device shown in the figure mounts two substrates 2 on a fixed frame 1, controls the substrate spacing to be 2 mm, then adds the modified sol 4 into the gas injection device, injects the sol into the space between the two substrates with the gas injection device, and pushes the injected sol to bubble with a stable nitrogen flow rate of 250 mL / min, so that it slides evenly on the substrate surface, and deposits a SiO2 film with a water contact angle of 45.59°, as shown in FIG. Figure 5 shown.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 6 is that no citric acid solution is added in step 1, and the remaining steps are consistent with Example 6. The water contact angle of the SiO2 film finally obtained is 145.81°, and the hydrophobicity is further improved, but the film hardness of the SiO2 film is 2H.
[0075] Figure 3 The graph of the refractive index of SiO2 films prepared in Examples 1 to 5 and Comparative Example 1 as a function of the MTES / TEOS molar ratio is shown in FIG. Figure 3 It can be seen that the refractive index of the sample without MTES in Comparative Example 1 is relatively high at about 1.15; as the amount of MTES added gradually increases, the refractive index of the sample with MTES gradually decreases. When the MTES content in Example 1 is 0.07 mL, the refractive index of the SiO2 film reaches the lowest value of 1.08; Figure 4 It can be seen that in Example 1, when the MTES content is 0.07 mL, the water contact angle of the SiO2 film is 124.99°, and the hydrophobicity is good. Figure 5 It can be seen that the contact angle of the sample without MTES in Comparative Example 1 is 45.59°, which is poor in hydrophobicity. In addition, due to the introduction of citric acid in Example 6, the film hardness of the SiO2 film is improved to 3H; in Example 7, citric acid is introduced and the SiO2 film is post-treated, and its hydrophobicity is further improved; in Comparative Example 2, since no citric acid solution is added, the film hardness of the SiO2 film prepared is relatively low.
[0076] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing an ultra-low refractive index anti-reflection film, characterized in that: The following steps are involved: Step 1: Mix polyacrylic acid, anhydrous ethanol and ammonia water, then add a certain amount of tetraethyl orthosilicate to react and age to obtain a hollow SiO2 nanosphere sol; Step 2: adding methyltriethoxysilane to the aged hollow SiO2 nanosphere sol, stirring the mixture thoroughly, and standing the mixture to obtain a modified sol; Step 3: Use a plasma cleaning machine to perform plasma cleaning on the substrate, and then use the constructed film blowing device to plate the modified sol on the substrate to form a thin film.
2. The method for preparing an ultra-low refractive index anti-reflection film according to claim 1, characterized in that: In the step 1, the mass volume ratio of polyacrylic acid, anhydrous ethanol, ammonia water and tetraethyl orthosilicate is 0.01-1 g:150-200 mL:5-15 mL:1 mL.
3. The method for preparing the ultra-low refractive index anti-reflection film according to claim 1, characterized in that: In the step 1, when adding ethyl orthosilicate, 0.2 mL of ethyl orthosilicate is added every 1 hour, and the mixture is aged for 48 to 72 hours.
4. The method for preparing the ultra-low refractive index anti-reflection film according to claim 1, characterized in that: In the step 2, the amount of methyltriethoxysilane added is 0.1-1 mL, stirred at 30° C. for 2 h, and aged for 7 days.
5. The method for preparing the ultra-low refractive index anti-reflection film according to claim 1, characterized in that: In the step three, the plasma cleaning power is 30W and the cleaning time is 5 minutes.
6. The method for preparing an ultra-low refractive index anti-reflection film according to claim 1, characterized in that: The specific steps of step three are: use the constructed film blowing device to fix the substrate, control the substrate spacing to 2 mm, inject an appropriate amount of sol with a syringe, slowly push the syringe to make the sol bubble slowly, and use a stable nitrogen flow rate of 250 mL / min to push the injected sol to bubble, so that it slides evenly on the substrate surface to coat an ultra-low refractive index SiO2 film.
7. A film blowing device constructed according to the preparation method according to any one of claims 1 to 6, characterized in that: include: A fixed frame is provided on which two substrates are detachably connected. A gas injection device is arranged above the substrates, and the modified sol is contained in the gas injection device.
8. The method for preparing an ultra-low refractive index anti-reflection film according to any one of claims 1 to 6, characterized in that: In the step 1, polyacrylic acid, anhydrous ethanol and ammonia water are mixed and stirred evenly, and then a certain amount of tetraethyl orthosilicate and citric acid solution are added to react. When tetraethyl orthosilicate is added, 0.2 mL of tetraethyl orthosilicate is added every 1 hour, and the concentration of the citric acid solution is 5-10wt%. When the citric acid solution is added, 0.2 mL is also added together with the tetraethyl orthosilicate every 1 hour, and the citric acid solution is aged to obtain a hollow SiO2 nanosphere sol.
9. The method for preparing an ultra-low refractive index anti-reflection film according to any one of claims 1 to 6, characterized in that: After the SiO2 film is prepared, it is post-processed, including the following steps: S1, dissolving a small molecule fluorine-containing compound and polyethyl methacrylate in toluene to prepare a spraying liquid; S2. Use a low-pressure sprayer to evenly spray the spray liquid onto the SiO2 film.
10. The method for preparing an ultra-low refractive index anti-reflection film according to claim 9, characterized in that: The small molecule fluorine-containing compound is one or more of hexafluorobutyl acrylate, hexafluorobutyl methacrylate or heptafluorobutyl acrylate, and the mass ratio of the small molecule fluorine-containing compound, ethyl methacrylate and toluene is 0.5-1:0.1-0.5:100.
Citation Information
Patent Citations
Gold-nanoparticle-contained mesoporous composite film electrode and preparation method and application thereof.
CN110196271A
An etching solution for a silicon dioxide thin film
CN111471463B